Crystal structure of 7-(4-methylphenyl)imidazo[1,2-a][1,3,5]triazin-4-amine, C12H11N5 - Lim, Felicia Phei Lin; Dolzhenko, Anton V; Halcovitch, Nathan R.; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C12H11N5, monoclinic, P21/n (no. 14), a=7.3455(1) Å, b=12.2470(1) Å, c=12.1689(1) Å, β=103.505(1)°, V =1064.45(2) Å3, Z =4, Rgt(F)=0.0365, wRref(F2)=0.0987, T =100 K.